Managerial ownership of voting rights - DeAngelo, Harry; DeAngelo, Linda (Journal of Financial Economics, 1985)
Managers of firms with dual classes of common stock can choose different quantities of votes for a given cash flow interest by choosing different quantities of the two securities. We study managerial stock holdings in 45 dual class firms and find that vote ownership per se is an important motivation for these holdings in that corporate officers and their families hold a median 56.9% of the votes and 24.0% of the common stock cash flows. We also find significant family involvement in many sample firms, and document four case studies in which explicit acquisition premiums were paid for superior voting shares.